The Effective and Influential Role of Military Companies’ Private Security and its Role in International Relations - Jumaa , Fadi A; Asfour , Bara (Journal of Ecohumanism, 2024)
Private military and security companies are now an integral part of modern warfare. These are entities that are created in the form of commercial companies that seek to make a profit in exchange for providing services in the military and security field to countries that request those services, which has made them one of the most important actors in the international relations process. One of the most important risks to international human law is private military and security companies that take advantage of their “bad” reputation in a fragmented market. They are increasingly hired by countries to work in areas experiencing armed conflict, and are becoming even more attractive because their members work outside the country. The official regular forces of states, and therefore it is not easy to hold them responsible for the violations they commit. However, its presence still raises controversy, and its participation as a private party in the conflict between states is not without raising questions about this issue and the legal aspect of this particular issue.